2011
DOI: 10.2478/v10168-011-0062-4
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Aperture Technique Applied to Tissue Attenuation Imaging

Abstract: The attenuating properties of biological tissue are of great importance in ultrasonic medical imaging. Investigations performed in vitro and in vivo showed the correlation between pathological changes in the tissue and variation of the attenuation coefficient. In order to estimate the attenuation we have used the downshift of mean frequency (fm) of the interrogating ultrasonic pulse propagating in the medium. To determine the fm along the propagation path we have applied the fm estimator (I/Q algorithm adopted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
(6 reference statements)
0
3
0
Order By: Relevance
“…By applying their theory, it is possible to obtain the resonance-dependent phase velocity and sound damping factor in bubbly water medium at low frequencies. Despite the extensive applications of sound attenuation, not only in underwater sound propagation but also in the areas of biological studies like that reported by Klimonda [20], research on sound attenuation especially at low-frequency range has not been developed enough to fulfill the industrial and medical requirements. In underwater acoustics, almost all of the studies have concentrated on one or two effective parameters.…”
Section: Introductionmentioning
confidence: 99%
“…By applying their theory, it is possible to obtain the resonance-dependent phase velocity and sound damping factor in bubbly water medium at low frequencies. Despite the extensive applications of sound attenuation, not only in underwater sound propagation but also in the areas of biological studies like that reported by Klimonda [20], research on sound attenuation especially at low-frequency range has not been developed enough to fulfill the industrial and medical requirements. In underwater acoustics, almost all of the studies have concentrated on one or two effective parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Singular Spectrum Analysis (SSA) is a relatively novel but powerful technique in time series analysis and forecasting that has been developed and applied to many practical problems (see, for example, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…The increase of the statistical independence of the image lines can be achieved through Synthetic Aperture Focusing Technique (SAFT) which, unlike the Classical Beamforming (CB), provides high image resolution in the whole scanned area. Some results of this approach can be found in our previous work (Klimonda et al, 2011). Another approach is to improve the attenuation estimates by means of compounding techniques.…”
Section: Introductionmentioning
confidence: 99%